OPINIONS OF STUDENTS AND TEACHERS ABOUT THE POSSIBILITY OF SECONDARY SCHOOL TURKISH COURSES IN DISTANCE EDUCATION - SARICI , Cemil; ALTINKAYNAK , Mehmet; TÜRKSOY , Saliha (SSD Journal, 2023)
In this research, it is aimed to contribute to the literature about the distance education process in Turkish lesson teaching by investigating the effects of the distance education process, which continues in line with the special objectives of the Turkish lesson curriculum, on the achievements of the secondary school Turkish lesson level, and whether the students gain the course goals and objectives. The research was studied as a quantitative research based on the opinions of 15 Turkish language teachers working in the official secondary schools of Kartal district of Istanbul and 40 students in the same schools. As a research model, a study was conducted to determine the situation by adhering to a descriptive research model, one of the survey models. According to the data revealed in the research, the survey questions were grouped into two sub-categories for teacher-student evaluations. As a result of the research; It was found that the students did not have difficulty in adapting to the distance Turkish lesson, the use of the Internet was also positive in terms of finding resources, and on the other hand, the teachers evaluated this process positively in terms of applying new methods and new teaching methods and improving themselves. It has been determined that students and teachers do not have difficulty in adapting to the process in the implementation of Turkish lessons with the distance education method, and it has emerged as an alternative to traditional teaching methods in terms of solving the problems that arise in the process and ensuring continuity in education.